2008
DOI: 10.1159/000111724
|View full text |Cite
|
Sign up to set email alerts
|

Do Weather Conditions Influence the Onset of Renal Colic? A Novel Approach to Analysis

Abstract: Background/Aim: To investigate the seasonal variations of the incidence of renal colic by a computerized analysis of cyclic climatic features. Methods: 1,163 consecutive patients with acute renal colic were studied. Eigendecomposition and signal reconstruction of district temperature and humidity were performed to establish any cyclic variation. Average temperatures and humidity values were calculated at time periods of 15, 30, 45 and 60 days preceding each renal colic. Results: Patients were allocated to grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
5
41
1
3
Order By: Relevance
“…There are several international studies that support this fact [6,7,8,9,10,11,12,13]. A similar study was conducted and published with respect to a different area in Spain; however, the number of cases is much lower than the one presented in this paper [1].…”
Section: Introductionsupporting
confidence: 53%
“…There are several international studies that support this fact [6,7,8,9,10,11,12,13]. A similar study was conducted and published with respect to a different area in Spain; however, the number of cases is much lower than the one presented in this paper [1].…”
Section: Introductionsupporting
confidence: 53%
“…Chen et al showed a seasonal trend, peaking in July, in the monthly urinary calculi attack rates in a retrospective study on a Taiwanese population [30]. Boscolo-Berto et al studied 1163 consecutive patients with acute renal colic, and found an association between the onset of symptoms and exposure to hot and dry weather, particularly for temperatures above 27°C and humidity below 45% [31]. In a survey of cases of renal colic in an urban ED, Cupisti et al found a seasonal distribution, peaking in July [32].…”
Section: Introductionmentioning
confidence: 99%
“…This also conforms with previous studies as Taha2 concluded that higher temperatures rather than Ramadan fasting appeared to be a risk factor for urinary tract stones. Boscolo-Berto et al14 concluded that there is an association between hot and dry climate and increased urinary tract stone formation. A different study also concluded that urinary tract stone admissions increased during the hottest months of the year, and started declining starting from Septemer 15.…”
Section: Discussionmentioning
confidence: 99%